Pengembangan Asesmen Kinerja Keterampilan Inquiry Laboratory pada Permasalahan Biologi Abad ke-21 - Rahmawati, Rahmawati; Wulan, Ana Ratna; Kusnadi, Kusnadi (Jurnal Paedagogy, 2022)
This study aims to develop an inquiry laboratory skill assessment on 21st Century Biological Problems. The assessment tool developed is a non-test assessment in the form of tasks and rubrics. The research and development method (R&D) was used in this study. The subjects of this research were 30 students from one of the public high schools in Banten Province. This research instrument used performance assessment tools in tasks and rubrics, while the data analysis technique used descriptive statistics and data collection purposive sampling. The study showed that the validity of Aiken’s V is 0.53. It can be said that the performance assessment tool is declared valid. The reliability value had an average measure value of 0.778. Moreover, the ICC (Interclass Correlation Coefficient) value assessed by three raters was categorized as moderate or moderate reliability. Based on the results of data analysis, the resulting instrument is ready to be used directly in measuring learning outcomes or as an assessment prototype for further development, especially in measuring students’ laboratory inquiry abilities.